SOSIALISASI PENINGKATAN PRODUKSI TANAMAN MANGGIS DIKAMPUNG TEMATIK MANGGIS LIMAU MANIS KECAMATAN PAUH KOTA PADANG - Obel Obel; Yulmira Yanti; Meisilva Erona S; Ihsan R.A; Saibi Saibi; Fachrizky Erdi Prawira (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
The government carries out various policies and strategies to support the development of horticulture in Indonesia. One of them is the development of Horticultural Villages such as the Manggis Thematic Village in accordance with the local wisdom of each region which is located in the Limau Manis sub-district, Pauh District, Padang City. Apart from producing mangosteen fruit, this thematic village has also become a tourist icon and can certainly strengthen West Sumatra's position as the largest mangosteen producing area in Indonesia. However, many of the mangosteen plants in this thematic village are old so the quantity and quality do not decline. Apart from that, there is no optimal management from cultivation to harvest. For this reason, it is necessary to socialise the technology to increase mangosteen productivity which aims to increase the knowledge of Tunas Harapan Limau Manis farmer group members in increasing mangosteen production in Kampung Tematik Manggis Limau Manis, Pauh sub-district, Padang city. The activity method used is the socialisation method to members of the Tunas Harapan farmer group. The results of the activity were an increase in the knowledge of farmer group members by 82.8% in applying mangosteen plant management technology to increase mangosteen productivity in the Manggis Limau Manis Thematic village. Apart from that, the activities carried out were also in accordance with community needs and 65% of farmer group members stated that they were very satisfied and that further activities were needed in the future.